1996
DOI: 10.1111/j.1445-5994.1996.tb02938.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult asthma and gastro‐oesophageal reflux: the effects of omeprazole therapy on asthma

Abstract: Omeprazole 40 mg daily improved evening PEFR in asthma patients with GOR. However, asthma symptoms, inhaled beta 2-agonist use and histamine bronchial responsiveness did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 13 publications
0
48
0
2
Order By: Relevance
“…Attempts were made to contact study authors for additional information needed for full analysis of their data. [12][13][14][15][16] Results…”
Section: Analysis Of Therapeutic Gainmentioning
confidence: 99%
“…Attempts were made to contact study authors for additional information needed for full analysis of their data. [12][13][14][15][16] Results…”
Section: Analysis Of Therapeutic Gainmentioning
confidence: 99%
“…Asthma symptoms also correlated with esophageal pH events on 24-h esophageal pH monitoring [11] . Previous studies on the effect of antireflux therapy on asthma have shown inconsistent results [12][13][14][15][16][17][18][19][20][21][22][23][24] . Most of these studies have been done in small groups of patients with different proton-pump inhibitors and were done for short durations of anti-reflux therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies dealing with asthma outcome and medical anti-reflux therapy. Field and Sutherland (1998) reviewed the previously published data on medical anti-reflux therapy with H 2 -receptor blockers (H 2 blockers), cimetidine (Goodall et al 1981;Larrain et al 1991) and ranitidine (Harper et al 1987;Nagel et al 1988;Ekstrom et al 1989;Gustaffson et al 1992), and with a proton pump inhibitor (PPI) omeprazole (Ford et al 1994;Meier et al 1994;Harding et al 1996;Teichtahl et al 1996), showing that asthma symptoms were improved. Kiljander (2003) suggested that, in the management of GERD-related asthma, PPIs other than omeprazole should be used at double the standard dose.…”
mentioning
confidence: 99%